2008
DOI: 10.1096/fj.08-106302
|View full text |Cite
|
Sign up to set email alerts
|

FHL2 mediates dexamethasone‐induced mesenchymal cell differentiation into osteoblasts by activating Wnt/β‐catenin signaling‐dependent Runx2 expression

Abstract: The differentiation of bone marrow mesenchymal stem cells (MSCs) into osteoblasts is a crucial step in bone formation. However, the mechanisms involved in the early stages of osteogenic differentiation are not well understood. In this study, we identified FHL2, a member of the LIM-only subclass of the LIM protein superfamily, that is up-regulated during early osteoblast differentiation induced by dexamethasone in murine and human MSCs. Gain-of-function studies showed that FHL2 promotes the expression of the os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
126
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(131 citation statements)
references
References 57 publications
5
126
0
Order By: Relevance
“…Total RNAs were isolated and relative, mRNA levels were evaluated by quantitative PCR analysis using microfluidic cards (Applied Biosystems) or LightCycler (Roche Applied Science) and normalized to 18S rRNA as described in ref. 36.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Total RNAs were isolated and relative, mRNA levels were evaluated by quantitative PCR analysis using microfluidic cards (Applied Biosystems) or LightCycler (Roche Applied Science) and normalized to 18S rRNA as described in ref. 36.…”
Section: Methodsmentioning
confidence: 99%
“…Viral production was performed as described in ref. 36. For transduction, subconfluent cells were incubated with lentivirus and 4 g/mL polybrene (Sigma) for 48 h.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Numerous in vitro studies have demonstrated the effect of osteoinductive treatment combining dexamethasone, ascorbic acid, and betaglycerophosphate (βGP) on MSC osteogenesis. Dexamethasone induces osteogenesis in vitro through activating WNT/ β-catenin signalling-dependent Runx2 expression, 5 whereas ascorbic acid increases collagen type 1 secretion. 6,7 βGP provides inorganic phosphate (Pi) that facilitates intracellular signalling molecules.…”
Section: Introductionmentioning
confidence: 99%